2003
DOI: 10.1074/jbc.m302842200
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Antigen 1-mediated Binding of Hepatitis B Virus to Hepatocytes Does Not Involve the Hepatic Serpin Clearance System

Abstract: The cellular receptor for hepatitis B virus (HBV)has not yet been identified. A recent candidate is a homologue of squamous cell carcinoma antigen 1 (SCCA1), a serpin. This study confirms that transfection of SCCA1 into mammalian cells (both hepatocyte-derived and of non-hepatocyte origin) results in increased HBV binding. Furthermore, virus bound to transfected cells is protected significantly from degradation by trypsin (75% compared with 30% in untransfected cells). The possibility that HBV enters cells via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…To explore the effect of the RSL of SERPINB3 in the induction of the TGF-b1 gene, previously described deletion loop mutants of SERPINB3, 28 were also used for cell transfection. The following vectors showing lack of inhibition of target proteinases were chosen: Mutant A (deletion of total hinge region of RSL-SERPINB3), Mutant B (deletion of total RSL-SERPINB3), and Mutant C (Mutation of the P14 codon from alanine to arginine) ( Figure 6).…”
Section: Construction Of Serpinb3 Expression Vectorsmentioning
confidence: 99%
“…To explore the effect of the RSL of SERPINB3 in the induction of the TGF-b1 gene, previously described deletion loop mutants of SERPINB3, 28 were also used for cell transfection. The following vectors showing lack of inhibition of target proteinases were chosen: Mutant A (deletion of total hinge region of RSL-SERPINB3), Mutant B (deletion of total RSL-SERPINB3), and Mutant C (Mutation of the P14 codon from alanine to arginine) ( Figure 6).…”
Section: Construction Of Serpinb3 Expression Vectorsmentioning
confidence: 99%
“…30 The hepatotropic specificity of HBV and consequently also the L nanoparticles, is determined by the interaction of the HBsAg with an elusive cellular receptor, although several candidate receptors or co-receptors have been proposed, including annexin V 31 and squamous cell carcinoma antigen-1 homolog (SCCA-1). 32 L nanoparticles are well tolerated and do not appear to induce serious adverse effects (Table 1, Figure 2). Furthermore, L nanoparticles by themselves have no effect on tumor suppression or progression (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…One of these groups first isolated SCCA1 as a ligand of the tetrameric pre‐S1 (21–47) peptide and showed that expression of SCCA1 enhances HBV infection and that recombinant SCCA1 inhibits HBV infection [10]. Another group demonstrated that the SCCA1‐mediated HBV infection does not involve the hepatic serpin clearance system [11]. The in vitro experiments described in the present study (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…2C: d,e and D). Taken together, these results indicate that SCCA1 is capable of interacting directly with BNC, as well as with HBV [10,11], and that the soluble SCCA1 protein inhibits the attachment of BNC to the surface of hepatic cells, presumably by competing with SCCA1 expressed on the cell surface.…”
Section: Resultsmentioning
confidence: 98%